Copolymer polyester resin and method for preparing same

A copolyester resin with controlled diol and dicarboxylic acid ratios enhances heat resistance, mechanical properties, and miscibility, addressing issues of transparency and viscosity, thereby improving economic efficiency and material compatibility.

JP2025500138APending Publication Date: 2025-01-09SK CHEMICALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024531468
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Existing polyester resins face challenges in achieving high heat resistance, mechanical properties, and miscibility without deteriorating transparency and viscosity, leading to issues such as material waste and increased processing time due to low miscibility with other resins.

Method used

A copolyester resin composition comprising specific ratios of diols, including isosorbide, cyclohexanedimethanol, and other diols, along with dicarboxylic acids, is developed to enhance heat resistance, mechanical properties, and miscibility, ensuring transparency is maintained.

Benefits of technology

The copolyester resin achieves improved heat resistance, mechanical properties, and miscibility, reducing material waste and processing time by ensuring excellent substitutability and homogeneous blending, making it suitable for applications like food containers and automobile parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500138000001
    Figure 2025500138000001
  • Figure 2025500138000002
    Figure 2025500138000002
  • Figure 2025500138000003
    Figure 2025500138000003
Patent Text Reader

Abstract

The present invention relates to a copolymer polyester resin and a preparation method thereof. In particular, according to one embodiment of the present invention, the copolymer polyester resin comprises a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, and by adjusting the amount of the first diol to the third diol or the fourth diol to the sixth diol contained in the diol component, the impact strength and intrinsic viscosity are controlled to be within an appropriate range without deteriorating the transparency, and therefore the miscibility is excellent. Therefore, the copolymer polyester resin can be used in various fields that require high impact strength and high heat resistance, such as packaging materials such as food containers and interior materials for vehicles, and can exhibit excellent properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Technical Field The present invention relates to a copolyester resin and a process for preparing the same. [Background technology]

[0002] Background technology Polyester resins are widely used as packaging materials such as fibers, films, sheets, and food containers, and as materials for automobile interior parts, due to their excellent mechanical properties and transparency. In particular, packaging materials that come into direct contact with food or materials such as automobile interior parts that are exposed to high temperatures require high heat resistance and mechanical properties, and research to increase these properties is ongoing.

[0003] Furthermore, in the process of preparing a polyester resin or using it as a raw material to prepare a product, when the polyester resin is replaced with another resin, the poor miscibility between the resins will result in a waste of raw materials or additional processing time, resulting in low economic efficiency.

[0004] In order to increase the heat resistance, mechanical properties, miscibility, etc. of polyester resin, it is blended with other resins or various additives are used. However, there is a limit to the increase in heat resistance, mechanical properties and miscibility. Even if the heat resistance or miscibility can be increased, there is a problem in that properties such as transparency or viscosity are deteriorated. Therefore, it is necessary to research polyester resins that can increase heat resistance and mechanical properties without deteriorating transparency and viscosity and can be easily replaced by excellent miscibility between resins.

[0005] As an example, Korean Patent Application Publication No. 2019-0064304 discloses a polyester resin having increased heat resistance by copolymerizing a dicarboxylic acid compound including isophthalic acid and a diol compound including a cyclohexyl bisphenol compound. However, when a cyclohexyl bisphenol compound is used, the crystallinity is reduced, which deteriorates the viscosity characteristics and mechanical properties such as impact strength of the polyester resin.

[0006] [Prior art document] [Patent documents] (Patent Document 1) Korean Patent Application Publication No. 2019-0064304 Summary of the Invention [Problem to be solved by the invention]

[0007] Disclosure of the Invention technical issues Therefore, the present invention aims to provide a copolymerized polyester resin and a process for preparing the same, which can increase heat resistance and mechanical properties without deteriorating transparency and viscosity characteristics, together with increased miscibility for easy substitutability. [Means for solving the problem]

[0008] Solution to the problem A copolymerized polyester resin according to one embodiment of the present invention includes a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, the diol component including (1) 10 mol% to 26 mol% of a first diol including isosorbide (ISB) or a derivative thereof, (2) 65 mol% to 80 mol% of a second diol including cyclohexanedimethanol (CHDM) or a derivative thereof, and (3) 8 mol% to 25 mol% of a third diol different from the first diol and the second diol, and a sample having a thickness of 6 mm prepared by blending two kinds of copolymerized polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0009] A copolymerized polyester resin according to another embodiment of the present invention includes a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, the diol component including (4) 15 mol% to 25 mol% of a fourth diol including 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof, (5) 70 mol% to 80 mol% of a fifth diol including cyclohexanedimethanol (CHDM) or a derivative thereof, and (6) 0 mol% to 10 mol% of a sixth diol different from the fourth diol and the fifth diol, and a sample having a thickness of 6 mm prepared by blending two types of copolymerized polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0010] A process for preparing a copolymerized polyester resin according to yet another embodiment of the present invention includes: (a) preparing a composition containing a diol component and a dicarboxylic acid or a derivative thereof; (b) subjecting the composition to an esterification reaction; and (c) subjecting the product of the esterification reaction to a polycondensation reaction, wherein the molar ratio (G / A) of the diol component and the dicarboxylic acid or a derivative thereof introduced in step (a) is 1.10 to 3.00. Effect of the Invention

[0011] Advantageous Effects of the Invention The copolymerized polyester resin according to one embodiment of the present invention includes a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, and the contents of the first to third diols or the fourth to sixth diols are controlled, thereby making it possible to increase heat resistance and mechanical properties without deteriorating transparency and viscosity characteristics. In particular, it is possible to increase the miscibility between resins, resulting in excellent substitutability.

[0012] Specifically, the copolymer polyester resin satisfies the above composition, and at the same time, the mixed resin obtained by blending two kinds of copolymer polyester resins having different compositions has a haze of less than 5.0% and has excellent compatibility. Therefore, when the copolymer polyester resin is substituted in a process for preparing the copolymer polyester resin or a process such as injection molding for preparing a product using the copolymer polyester resin as a raw material, it is economical because it can minimize the waste of raw materials and reduce the processing time or process steps.

[0013] Furthermore, when the copolymer polyester resin according to one embodiment of the present invention is applied to products that require high impact strength and high heat resistance, such as packaging materials such as food containers and automobile interior parts, it will be excellent in stability and quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] BEST MODE FOR CARRYING OUT THEINVENTION The present invention is described in detail below. The present invention is not limited to the disclosure given below, but may be modified in various forms without departing from the spirit of the present invention.

[0015] Throughout this specification, when a moiety is referred to as "comprising" certain elements, it is understood that other elements may be included, rather than excluding other elements, unless specifically stated otherwise.

[0016] All numbers and expressions relating to quantities of ingredients, reaction conditions, and the like used herein are understood to be modified by the term "about," unless otherwise specified.

[0017] In this specification, when an element is referred to as being formed "on" or "under" another element, it means not only that an element is formed directly "on" or "under" the other element, but also that an element is formed indirectly on or under the other element, with the other element sandwiched between them.

[0018] Throughout this specification, the terms first, second, etc. are used to describe various components. The components should not be limited by the terms. The terms are used only to distinguish one component from another.

[0019] Copolymer polyester resin A copolymerized polyester resin according to one embodiment of the present invention includes a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, the diol component including (1) 10 mol% to 26 mol% of a first diol including isosorbide (ISB) or a derivative thereof, (2) 65 mol% to 80 mol% of a second diol including cyclohexanedimethanol (CHDM) or a derivative thereof, and (3) 8 mol% to 25 mol% of a third diol different from the first diol and the second diol, and a sample having a thickness of 6 mm prepared by blending two kinds of copolymerized polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0020] A copolymerized polyester resin according to another embodiment of the present invention includes a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, the diol component including (4) 15 mol% to 25 mol% of a fourth diol including 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof, (5) 70 mol% to 80 mol% of a fifth diol including cyclohexanedimethanol (CHDM) or a derivative thereof, and (6) 0 mol% to 10 mol% of a sixth diol different from the fourth diol and the fifth diol, and a sample having a thickness of 6 mm prepared by blending two types of copolymerized polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0021] Specifically, the copolymerized polyester resin is a resin in which a diol component and a dicarboxylic acid or a derivative thereof are copolymerized, and it contains a repeating unit derived from the diol component and a repeating unit derived from the dicarboxylic acid or a derivative thereof.

[0022] According to an embodiment of the present invention, the diol component includes a first diol including isosorbide (ISB) or a derivative thereof in an amount of 10 mol % to 26 mol % based on the total number of moles of the diol component. More specifically, the copolymerized polyester resin includes 10 mol % to 26 mol % of residues derived from the first diol based on the total diol-derived residues of the copolymerized polyester resin.

[0023] For example, the copolymerized polyester resin may contain the first diol in an amount of 10 mol% to 25 mol%, 10 mol% to 23 mol%, 10 mol% to 20 mol%, 11 mol% to 25 mol%, 11 mol% to 23 mol%, 11 mol% to 20 mol%, 12 mol% to 25 mol%, 16 mol% to 25 mol%, 18 mol% to 25 mol%, or 20 mol% to 25 mol% based on the total number of moles of the diol component.

[0024] Since the content of the first diol satisfies the above range, it is possible to increase the mechanical properties and the miscibility between resins without deteriorating the heat resistance. Specifically, if the content of the first diol is less than 10 mol%, the glass transition temperature of the copolymerized polyester resin may decrease, which deteriorates the heat resistance. If the content of the first diol is more than 26 mol%, the miscibility of the copolymerized polyester resin may decrease significantly, which deteriorates the substitutability.

[0025] Furthermore, the diol component contains a second diol containing cyclohexanedimethanol (CHDM) or a derivative thereof in an amount of 65 mol % to 80 mol % based on the total number of moles of the diol component. Specifically, the copolymerized polyester resin contains 65 mol % to 80 mol % of residues derived from the second diol based on the total diol-derived residues of the copolymerized polyester resin.

[0026] For example, the copolymerized polyester resin may contain the second diol in an amount of 65 mol % to 78 mol %, 65 mol % to 77 mol %, or 70 mol % to 77 mol % based on the total number of moles of the diol component.

[0027] Since the content of the second diol satisfies the above range, it is possible to increase the crystallinity, thereby increasing mechanical properties such as viscosity characteristics and impact strength without deteriorating heat resistance. Specifically, when the content of the second diol is less than 65 mol%, the mechanical properties such as viscosity characteristics and impact strength may be deteriorated, which deteriorates the durability, productivity and life characteristics of the product prepared from the copolymerized polyester resin. When the content of the second diol is more than 80 mol%, the crystallinity may increase due to the reactivity of the copolymerized polyester resin with the first diol, which significantly deteriorates the transparency and especially the miscibility.

[0028] The diol component includes a third diol that is different from the first diol and the second diol.

[0029] The third diol may be at least one selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-propanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, neopentyl glycol and derivatives thereof. Ethylene glycol may be preferred in that it can increase heat resistance and miscibility without deteriorating transparency and mechanical properties, but is not limited thereto.

[0030] The copolymerized polyester resin contains the third diol in an amount of 8 mol % to 25 mol % based on the total number of moles of the diol component. Specifically, the copolymerized polyester resin contains 8 mol % to 25 mol % of residues derived from the third diol based on the total diol-derived residues of the copolymerized polyester resin.

[0031] For example, the copolymerized polyester resin may contain the third diol in an amount of 8 mol % to 24 mol %, 8 mol % to 22 mol %, 8 mol % to 19 mol %, or 10 mol % to 25 mol % based on the total number of moles of the diol component.

[0032] According to another embodiment of the present invention, the diol component comprises a fourth diol comprising 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof in an amount of 15 mol% to 25 mol% based on the total number of moles of the diol component. More specifically, the copolymerized polyester resin comprises 15 mol% to 25 mol% of residues derived from the fourth diol based on the total diol-derived residues of the copolymerized polyester resin.

[0033] For example, the copolymerized polyester resin may contain the fourth diol in an amount of 16 mol % to 24 mol %, 16 mol % to 22 mol %, 18 mol % to 21 mol %, or 17 mol % to 23 mol % based on the total number of moles of the diol component.

[0034] Since the content of the fourth diol satisfies the above range, it is possible to increase the mechanical properties and the miscibility between resins without deteriorating the heat resistance. Specifically, if the content of the fourth diol is less than 15 mol%, the glass transition temperature of the copolymerized polyester resin may be low, which deteriorates the heat resistance. If the content of the fourth diol is more than 25 mol%, the miscibility of the copolymerized polyester resin may be significantly reduced, which deteriorates the substitutability.

[0035] Furthermore, the diol component contains a fifth diol containing cyclohexanedimethanol (CHDM) or a derivative thereof in an amount of 70 mol % to 80 mol % based on the total number of moles of the diol component. Specifically, the copolymerized polyester resin contains 70 mol % to 80 mol % of residues derived from the fifth diol based on the total diol-derived residues of the copolymerized polyester resin.

[0036] For example, the copolymerized polyester resin may contain the fifth diol in an amount of 70 mol % to 78 mol %, 70 mol % to 75 mol %, or 70 mol % to 72 mol % based on the total number of moles of the diol component.

[0037] Since the content of the fifth diol satisfies the above range, it is possible to increase mechanical properties such as viscosity characteristics and impact strength without deteriorating heat resistance. Specifically, if the content of the fifth diol is less than 70 mol%, mechanical properties such as viscosity characteristics and impact strength may be deteriorated, which deteriorates the durability, productivity and life characteristics of the product prepared from the copolymerized polyester resin. If the content of the fifth diol is more than 80 mol%, the crystallinity may increase due to the reactivity of the copolymerized polyester resin with the fourth diol, which significantly deteriorates transparency and especially miscibility.

[0038] The diol component includes a sixth diol different from the fourth diol and the fifth diol.

[0039] The sixth diol may be at least one selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-propanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, neopentyl glycol and derivatives thereof. Ethylene glycol may be preferred in that it can increase heat resistance and miscibility without deteriorating transparency and mechanical properties, but is not limited thereto.

[0040] The copolymerized polyester resin contains the sixth diol in an amount of 0 mol % to 10 mol % based on the total number of moles of the diol component. Specifically, the copolymerized polyester resin contains 0 mol % to 10 mol % of residues derived from the sixth diol based on the total diol-derived residues of the copolymerized polyester resin.

[0041] For example, the copolymer polyester resin may contain the sixth diol in an amount of 1 mol % to 10 mol %, 3 mol % to 10 mol %, 5 mol % to 10 mol %, or 8 mol % to 10 mol % based on the total moles of the diol component.

[0042] According to one embodiment of the present invention, it is important to adjust the contents of the first to third diols or the fourth to sixth diols in the copolymerized polyester resin.

[0043] Specifically, in order to achieve the desired physical properties in the present invention, more specifically, to increase the heat resistance, mechanical properties, and miscibility without deteriorating the transparency and viscosity properties, it is very important to adjust the content of the first to third diols or the fourth to sixth diols in the copolymer polyester resin. Therefore, according to one embodiment of the present invention, since the content of the first to third diols or the fourth to sixth diols satisfies the above respective ranges, it is possible to increase the heat resistance, mechanical properties, and miscibility together with the transparency and viscosity properties.

[0044] In particular, isosorbide has been used in the past because it can increase heat resistance by increasing glass transition temperature.When isosorbide is used, it can increase heat resistance, but there is a problem of deterioration of quality such as reduction in transparency, color characteristics or mechanical properties, or reduction in miscibility, which deteriorates substitutability and productivity.In addition, isosorbide has low reactivity, so it is difficult to form a high-viscosity polyester resin.Therefore, in order to achieve the desired physical properties in the present invention, it is very important to control the composition ratio between diol components.

[0045] Specifically, the composition ratio of the second diol to the first diol (second diol (mol%) / first diol (mol%)) may be 2.30 to 7.45, 2.35 to 7.20, 2.55 to 7.15, 2.60 to 7.00, 3.00 to 7.20, 3.55 to 7.15, 3.55 to 7.00, or 3.50 to 6.00. The composition ratio of the third diol to the second diol (third diol (mol%) / second diol (mol%)) may be 2.50 to 15.00, 2.55 to 13.00, 2.60 to 11.50, 2.65 to 10.00, 2.65 to 9.50, 2.71 to 9.00, 3.50 to 9.20, or 6.25 to 9.00. The composition ratio of the first diol to the third diol (first diol (mol %) / third diol (mol %)) can be 0.25 to 6.00, 0.25 to 4.50, 0.30 to 3.55, 0.35 to 3.00, 0.40 to 2.75, 0.46 to 2.5, 0.50 to 2.55, or 0.85 to 2.50.

[0046] The composition ratio of the fifth diol to the fourth diol (fifth diol (mol %) / fourth diol (mol %)) may be 2.55 to 7.05, 2.65 to 6.45, 2.70 to 5.95, 2.75 to 5.25, 2.85 to 4.90, 2.95 to 4.55, 3.00 to 4.15, 3.15 to 4.05, 3.25 to 3.90, or 3.30 to 3.65. The composition ratio of the fifth diol to the sixth diol (fifth diol (mol%) / sixth diol (mol%)) may be 4.50 to 10.00, 4.75 to 9.50, 4.95 to 9.00, 5.25 to 8.65, 5.55 to 8.20, 5.80 to 8.05, 6.15 to 7.90, 6.45 to 7.75, or 6.85 to 7.45. The composition ratio of the fourth diol to the sixth diol (fourth diol (mol%) / sixth diol (mol%)) may be 0.50 to 4.50, 0.55 to 3.95, 0.70 to 3.50, 0.85 to 2.95, 1.05 to 2.50, 1.55 to 2.25, or 1.75 to 2.05.

[0047] Since the composition ratios of the first to third diols or the fourth to sixth diols satisfy the above-mentioned respective ranges, it is possible to further improve the heat resistance, mechanical properties, and miscibility without deteriorating the transparency and viscosity characteristics.

[0048] Further, the dicarboxylic acid or its derivative component refers to a main monomer constituting the copolymerized polyester resin together with the diol component. The dicarboxylic acid or its derivative component may preferably include an aromatic dicarboxylic acid or its derivative from the viewpoint of increasing heat resistance, but is not limited thereto.

[0049] As used herein, "dicarboxylic acid or a derivative thereof" refers to at least one compound selected from the group consisting of dicarboxylic acids and derivatives of dicarboxylic acids.

[0050] Specifically, the "derivative of a dicarboxylic acid" may refer to an alkyl ester of a dicarboxylic acid or an anhydride of a dicarboxylic acid. For example, the alkyl ester may include, but is not limited to, an alkyl ester having 1 to 4 carbon atoms, such as monomethyl ester, monoethyl ester, dimethyl ester, diethyl ester, and dibutyl ester.

[0051] More specifically, the dicarboxylic acid or derivative thereof may be terephthalic acid or a derivative thereof, which may be a compound capable of reacting with a diol to form a terephthaloyl moiety, such as terephthalic acid, a monoalkyl terephthalate, a dialkyl terephthalate such as dimethyl terephthalate, or terephthalic anhydride.

[0052] According to one embodiment of the present invention, the dicarboxylic acid or its derivative may be terephthalic acid or its derivative.

[0053] Specifically, the dicarboxylic acid or derivative thereof may consist solely of terephthalic acid or a derivative thereof. More specifically, the dicarboxylic acid or derivative thereof may be terephthalic acid or dimethyl terephthalate.

[0054] When the dicarboxylic acid is terephthalic acid, it may be preferable in that it is possible to increase the residual rate of the ISB and increase the mechanical properties such as impact strength and the intrinsic viscosity properties. Furthermore, when the dicarboxylic acid derivative is dimethyl terephthalate, the residual rate of the ISB may be slightly lower than when terephthalic acid is used, but it may be preferable in that it is possible to further increase the mechanical properties such as impact strength and the intrinsic viscosity properties.

[0055] For example, the copolyester resin may contain 100 mole % of residues derived from terephthalic acid or dimethyl terephthalate, based on the total acid-derived residues of the copolyester resin.

[0056] According to another embodiment of the invention, the dicarboxylic acid or derivative thereof comprises terephthalic acid or a derivative thereof, which may further comprise a dicarboxylic acid or a derivative thereof different from terephthalic acid or a derivative thereof.

[0057] Specifically, the dicarboxylic acid or derivative thereof may include terephthalic acid or a derivative thereof, which may further include at least one selected from the group consisting of an aromatic dicarboxylic acid or a derivative thereof having 8 to 14 carbon atoms and an aliphatic dicarboxylic acid or a derivative thereof having 4 to 12 carbon atoms.

[0058] The aromatic dicarboxylic acid or derivative thereof having 8 to 14 carbon atoms may be, for example, at least one selected from the group consisting of isophthalic acid, dimethyl isophthalate, phthalic acid, dimethyl phthalate, phthalic anhydride, naphthalene dicarboxylic acids such as 2,6-naphthalene dicarboxylic acid, dialkyl naphthalene dicarboxylates such as dimethyl-2,6-naphthalene dicarboxylate, and diphenyl dicarboxylic acid, but is not limited thereto.

[0059] The aliphatic dicarboxylic acid or derivative thereof having 4 to 12 carbon atoms may include linear, branched or cyclic aliphatic dicarboxylic acid or derivative thereof. For example, they may be at least one selected from the group consisting of cyclohexanedicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 1,3-cyclohexanedicarboxylic acid, cyclohexanedicarboxylates such as dimethyl-1,4-cyclohexanedicarboxylate and dimethyl-1,3-cyclohexanedicarboxylate, sebacic acid, succinic acid, isodecyl succinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid and azelaic acid, but are not limited thereto.

[0060] Furthermore, the dicarboxylic acid or derivative thereof may contain terephthalic acid or a derivative thereof in an amount of 90 mol % to 99 mol %, and at least one selected from the group consisting of an aromatic dicarboxylic acid or a derivative thereof having 8 to 14 carbon atoms different from terephthalic acid, and an aliphatic dicarboxylic acid or a derivative thereof having 4 to 12 carbon atoms, in an amount of 1 mol % to 10 mol %.

[0061] For example, the copolymerized polyester resin may contain residues derived from terephthalic acid or residues derived from dimethyl terephthalate in an amount of 90 mol % to 99 mol %, 92 mol % to 98 mol %, 93 mol % to 97 mol %, or 94 mol % to 96 mol %, and residues derived from isophthalic acid in an amount of 1 mol % to 10 mol %, 2 mol % to 8 mol %, 3 mol % to 7 mol %, or 4 mol % to 6 mol %, based on the total acid-derived residues in the copolymerized polyester resin.

[0062] According to one embodiment of the present invention, a sample having a thickness of 6 mm prepared by blending two kinds of copolyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0063] Specifically, the two types of copolymerized polyester resins may be two types of copolymerized polyester resins containing the first diol to the third diol, two types of copolymerized polyester resins containing the fourth diol to the sixth diol, or one type of copolymerized polyester resin containing the first diol to the third diol and one type of copolymerized polyester resin containing the fourth diol to the sixth diol.

[0064] Generally, various resins are used in the process of using copolymer polyester resin to manufacture products, specifically the injection molding process, so that if the miscibility between the resins is low, raw materials will be wasted or additional processing time will be required, resulting in low economic efficiency.

[0065] When the composition of the diol component and the dicarboxylic acid component, particularly the content of each diol component of the copolymerized polyester resin according to one embodiment of the present invention, satisfies the above range, it has excellent miscibility even if their respective contents are different from each other. Specifically, when two resins are blended with each other, if the miscibility between the resins is low, they are not homogeneously blended, so the haze value increases. However, in the copolymerized polyester resin according to one embodiment of the present invention, a sample having a thickness of 6 mm prepared by blending two copolymerized polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97, indicating excellent miscibility.

[0066] For example, the haze of a sample having a thickness of 6 mm prepared by blending two kinds of copolymer polyester resins having different compositions in a 1:1 weight ratio, when measured according to ASTM D1003-97, can be 4.9% or less, 4.5% or less, 4.2% or less, 4.1% or less, 3.9% or less, 3.8% or less, 3.5% or less, 3.1% or less, less than 3.0%, 2.8% or less, 2.7% or less, 2.5% or less, 2.1% or less, 1.8% or less, 1.5% or less, 0.9% or less, 0.6% or less, 0.4% or less, or 0.3% or less.

[0067] Furthermore, the copolymer polyester resin may have a glass transition temperature (Tg) of 98° C. to 115° C. For example, the glass transition temperature (Tg) of the copolymer polyester resin may be 99° C. to 115° C., 100° C. to 115° C., 100° C. to 114° C., 101° C. to 114° C., 103° C. to 115° C., 99° C. to 110° C., or 100° C. to 110° C.

[0068] Specifically, the glass transition temperature was measured as the first endothermic temperature in a second scan obtained by increasing the temperature of the copolyester resin to 280° C. at 10° C. / min under nitrogen, decreasing the temperature to 30° C. at −300° C. / min, and then increasing the temperature again to 280° C. at 10° C. / min under nitrogen.

[0069] A sample having a thickness of 6.4 mm prepared from the copolymer polyester resin may have an impact strength of 700 J / m or greater when measured according to ASTM D256. For example, a sample having a thickness of 6.4 mm prepared from the copolymer polyester resin may have an impact strength of 705 J / m or greater, 710 J / m or greater, 720 J / m or greater, 725 J / m or greater, 730 J / m or greater, 735 J / m or greater, 740 J / m or greater, 755 J / m or greater, or 760 J / m or greater when measured according to ASTM D256.

[0070] In the past, research has been continued to increase the heat resistance and impact strength of copolymer polyester resins. However, there is a limit to the increase in heat resistance and hydrolysis resistance. Even if the heat resistance or hydrolysis resistance can be increased, there is a problem that properties such as transparency and mechanical properties are deteriorated. Therefore, it has been difficult to increase all mechanical properties such as heat resistance, hydrolysis resistance, transparency and impact strength at the same time.

[0071] In particular, isosorbide is widely used because it can increase heat resistance by increasing the glass transition temperature, but it deteriorates transparency, color characteristics, and mechanical properties such as impact strength.

[0072] The copolymer polyester resin has excellent impact resistance since a sample prepared therefrom having a thickness of 6.4 mm has an impact strength of 700 J / m or more when measured according to ASTM D256. The impact strength varies sensitively with respect to the thickness of the sample, especially as the thickness of the sample becomes thicker. The impact strength of a sample prepared therefrom having a thickness of 3.2 mm, measured according to ASTM D256, was usually 310 J / m or less. In contrast, the copolymer polyester resin has excellent impact strength since a sample prepared therefrom having a thickness greater than that of the conventional resin meets the impact strength of 700 J / m or more. The copolymer polyester resin according to one embodiment of the present invention has excellent impact resistance since the composition and composition ratio of the diol component are adjusted within a specific range, and properties such as intrinsic viscosity and glass transition temperature are controlled as well.

[0073] Additionally, a sample having a thickness of 3.2 mm prepared from the copolymer polyester resin may have an impact strength of 800 J / m or greater when measured according to ASTM D256. For example, a sample having a thickness of 3.2 mm prepared from the copolymer polyester resin may have an impact strength of 820 J / m or greater, 850 J / m or greater, 855 J / m or greater, or 860 J / m or greater when measured according to ASTM D256.

[0074] The copolymer polyester resin may have an intrinsic viscosity (IV) of 0.64 to 0.78 dl / g. For example, the copolymer polyester resin may have an intrinsic viscosity (IV) of 0.65 dl / g to 0.78 dl / g, 0.64 dl / g to 0.76 dl / g, 0.64 dl / g to 0.75 dl / g, 0.68 dl / g to 0.78 dl / g, 0.70 dl / g to 0.78 dl / g, 0.70 dl / g to 0.75 dl / g, 0.72 dl / g to 0.78 dl / g, or 0.74 dl / g to 0.78 dl / g.

[0075] Since the intrinsic viscosity satisfies the above range, it is possible to increase mechanical properties such as impact strength. Specifically, even if the resin composition and content are the same, the mechanical properties, especially the impact strength properties, may vary depending on the intrinsic viscosity. Therefore, in order to increase mechanical properties such as impact strength without deteriorating properties such as transparency and heat resistance, it is important to control the intrinsic viscosity together with the resin composition and content.

[0076] According to one embodiment of the present invention, the copolymerized polyester resin may further comprise at least one additive selected from the group consisting of a colorant, a crystallization agent, an oxidation stabilizer, and a branching agent.

[0077] The colorant is an additive for enhancing the color properties of the copolymerized polyester resin. Commonly used colorants such as cobalt acetate and cobalt propionate can be used as the colorant as long as the effect of the present invention is not impaired.

[0078] Specifically, the colorant may be cobalt acetate, cobalt propionate, anthraquinones, perinones, azos, and methines. Commercially available toners such as Clariant's Polysynthren Blue RLS or Clariant's Solvaperm Red BB may be used.

[0079] Furthermore, the copolymer polyester resin may contain a colorant in an amount of 0.1 ppm to 30 ppm based on the total weight of the copolymer polyester resin. For example, the colorant may be used in an amount of 0.2 ppm to 30 ppm, 0.5 ppm to 25 ppm, 0.6 ppm to 23 ppm, or 0.8 ppm to 20 ppm based on the total weight of the copolymer polyester resin. Since the content of the colorant satisfies the above range, the color properties of the copolymer polyester resin may be sufficiently increased without deteriorating its mechanical properties.

[0080] The crystallization agent may include at least one selected from the group consisting of a crystal nucleating agent, a UV absorber, a polyolefin resin, a polyamide resin, and a polyalkylene resin.

[0081] Further, the copolymer polyester resin may contain a crystallization agent in an amount of 0.1 ppm to 10 ppm based on the total weight of the copolymer polyester resin. For example, the crystallization agent may be used in an amount of 0.2 ppm to 8 ppm, 0.5 ppm to 6 ppm, 1 ppm to 10 ppm, 2 ppm to 8 ppm, 3 ppm to 6 ppm, or 4 ppm to 6 ppm based on the total weight of the copolymer polyester resin.

[0082] The oxidation stabilizer may include at least one selected from the group consisting of a hindered phenol-based oxidation stabilizer, a phosphite-based oxidation stabilizer, and a thioether-based oxidation stabilizer.

[0083] Furthermore, the copolymer polyester resin may contain an oxidation stabilizer in an amount of 50 ppm to 3,000 ppm based on the total weight of the copolymer polyester resin. For example, the oxidation stabilizer may be used in an amount of 50 ppm to 2,700 ppm, 60 ppm to 2,400 ppm, 80 ppm to 2,200 ppm, 100 ppm to 2,000 ppm, 300 ppm to 2,000 ppm, 500 ppm to 1,900 ppm, or 750 ppm to 1,800 ppm based on the total weight of the copolymer polyester resin. Since the content of the oxidation stabilizer satisfies the above range, it is possible to further increase the miscibility.

[0084] Since the content of the oxidative stabilizer satisfies the above range, it is possible to effectively prevent the decrease in intrinsic viscosity that may occur in the subsequent process, and to prevent the decrease in physical properties such as impact strength as well. Specifically, if the content of the oxidative stabilizer is less than 50 ppm, the color properties may deteriorate in the subsequent process such as processing. If it exceeds 3,000 ppm, the polymerization reactivity may decrease, thereby deteriorating the viscosity properties.

[0085] The branching agent may include at least one selected from the group consisting of trimellitic anhydride, trimethylolpropane, and trimellitic acid.

[0086] Furthermore, the copolymer polyester resin may contain a branching agent in an amount of 100 ppm to 2,500 ppm based on the total weight of the copolymer polyester resin. For example, the branching agent may be used in an amount of 100 ppm to 2,000 ppm, 110 ppm to 1,800 ppm, 115 ppm to 1,500 ppm, 120 ppm to 1,200 ppm, or 130 ppm to 1,000 ppm based on the total weight of the copolymer polyester resin. Since the content of the branching agent meets the above range, the intrinsic viscosity can be more effectively controlled within a specific range.

[0087] Copolymer polyester mixed resin Another embodiment of the present invention provides a copolymerized polyester blend resin comprising a first copolymerized polyester resin and a second copolymerized polyester resin, each of which comprises a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, the diol component comprising: (1) 10 mol% to 26 mol% of a first diol comprising isosorbide (ISB) or a derivative thereof; (2) 65 mol% to 80 mol% of a second diol comprising cyclohexanedimethanol (CHDM) or a derivative thereof; and (3) 8 mol% to 25 mol% of a third diol different from the first diol and the second diol. A sample having a thickness of 6 mm prepared by blending the first copolymerized polyester resin and the second copolymerized polyester resin in a 1:1 weight ratio has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0088] According to yet another embodiment of the present invention, the copolymerized polyester mixed resin comprises a third copolymerized polyester resin and a fourth copolymerized polyester resin, each of which comprises a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, and the diol component comprises: (4) 15 mol% to 25 mol% of a fourth diol comprising 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof; (5) 70 mol% to 80 mol% of a fifth diol comprising cyclohexanedimethanol (CHDM) or a derivative thereof; and (6) 0 mol% to 10 mol% of a sixth diol different from the fourth diol and the fifth diol. A sample having a thickness of 6 mm prepared by blending the third copolymerized polyester resin and the fourth copolymerized polyester resin in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0089] The copolymer polyester mixed resin may include a first copolymer polyester resin and a second copolymer polyester resin, or a third copolymer polyester resin and a fourth copolymer polyester resin. Furthermore, the copolymer polyester mixed resin may include a first copolymer polyester resin and a third copolymer polyester resin. The first to fourth copolymer polyester resins have substantially the same composition and properties as those of the above-mentioned copolymer polyester resins, respectively.

[0090] Specifically, the first copolyester resin may have a different composition ratio from that of the second copolyester resin. More specifically, the content of each diol component of the first copolyester resin may be different from that of the second copolyester resin. The content of each dicarboxylic acid or its derivative component of the first copolyester resin may be different from that of each dicarboxylic acid or its derivative component of the second copolyester resin.

[0091] Furthermore, the third copolyester resin may have a composition ratio different from that of the fourth copolyester resin. More specifically, the content of each diol component of the third copolyester resin may be different from that of each diol component of the fourth copolyester resin. The content of each dicarboxylic acid or its derivative component of the third copolyester resin may be different from that of each dicarboxylic acid or its derivative component of the fourth copolyester resin.

[0092] A copolymerized polyester mixed resin according to yet another embodiment of the present invention includes a first copolymerized polyester resin including first to third diols and a third copolymerized polyester resin including fourth to sixth diols, and a sample having a thickness of 6 mm prepared by blending the first copolymerized polyester resin and the third copolymerized polyester resin in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0093] Specifically, a sample having a thickness of 6 mm prepared by blending a first copolyester resin and a second copolyester resin, a third copolyester resin and a fourth copolyester resin, or the first copolyester resin and a third copolyester resin in a 1:1 weight ratio has a haze of less than 5.0% when measured according to ASTM D1003-97.

[0094] For example, the haze of a sample having a thickness of 6 mm prepared by blending the first copolyester resin and the second copolyester resin, the third copolyester resin and the fourth copolyester resin, or the first copolyester resin and the third copolyester resin in a 1:1 weight ratio, when measured according to ASTM D1003-97, can be 4.9% or less, 4.5% or less, 4.3% or less, 4.2% or less, 4.1% or less, 4.0% or less, 3.9% or less, 3.8% or less, 3.5% or less, 3.1% or less, less than 3.0%, 2.8% or less, 2.7% or less, 2.5% or less, 2.1% or less, 1.8% or less, 1.5% or less, 0.9% or less, 0.6% or less, 0.4% or less, or 0.3% or less.

[0095] According to yet another embodiment of the present invention, the copolymer polyester mixed resin contains two kinds of copolymer polyester resins, so it can be easily adjusted to have desired physical properties, and a sample having a thickness of 6 mm prepared by blending them in a weight ratio of 1:1 has a haze of less than 5.0% when measured according to ASTM D1003-97, showing excellent compatibility.

[0096] Furthermore, the copolymerized polyester mixed resin may further include a copolymerized polyester resin containing a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, and the diol component includes (1) 10 mol% to 26 mol% of a first diol containing isosorbide (ISB) or a derivative thereof, (2) 65 mol% to 80 mol% of a second diol containing cyclohexanedimethanol (CHDM) or a derivative thereof, and (3) 8 mol% to 25 mol% of a third diol different from the first diol and the second diol.

[0097] Furthermore, the copolymerized polyester mixed resin may further include a copolymerized polyester resin containing a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, and the diol component includes (4) 15 mol% to 25 mol% of a fourth diol containing 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof, (5) 70 mol% to 80 mol% of a fifth diol containing cyclohexanedimethanol (CHDM) or a derivative thereof, and (6) 0 mol% to 10 mol% of a sixth diol different from the fourth diol and the fifth diol.

[0098] Specifically, the copolymerized polyester mixed resin according to another embodiment of the present invention may include three or more types of copolymerized polyester mixed resins.

[0099] Process for preparing copolymer polyester resin A process for preparing a copolymerized polyester resin according to yet another embodiment of the present invention includes: (a) preparing a composition containing a diol component and a dicarboxylic acid or a derivative thereof; (b) subjecting the composition to an esterification reaction; and (c) subjecting the product of the esterification reaction to a polycondensation reaction, wherein the molar ratio (G / A) of the diol component and the dicarboxylic acid or a derivative thereof introduced in step (a) is 1.10 to 3.00.

[0100] The copolymer polyester resin prepared according to the process for preparing a copolymer polyester resin has substantially the same composition and properties as those of the copolymer polyester resin described above.

[0101] Furthermore, the composition and process conditions can be adjusted so that the copolymerized polyester resin finally prepared according to the process for preparing the copolymerized polyester resin meets the above-mentioned properties such as transparency, heat resistance, hydrolysis resistance and mechanical properties.

[0102] First, a composition containing a diol component and a dicarboxylic acid or a derivative thereof component is prepared (step (a)).

[0103] Details regarding the diol component and the dicarboxylic acid or derivative thereof component are as described above.

[0104] The molar ratio (G / A) of the diol component to the dicarboxylic acid or its derivative component introduced in step (a) is 1.10 to 3.00. For example, the molar ratio (G / A) of the diol component to the dicarboxylic acid or its derivative component introduced in step (a) can be 1.15 to 2.85, 1.15 to 2.65, 1.18 to 2.63, 1.10 to 2.50, 1.18 to 2.63, 1.18 to 2.50, 1.10 to 2.20, 1.15 to 2.00, 1.18 to 1.55, 1.20 to 1.45, 1.18 to 1.40, 1.20 to 1.40, 1.25 to 1.40, or 1.30 to 1.40.

[0105] Since the molar ratio (G / A) of the diol component to the dicarboxylic acid or its derivative component satisfies the above range, the productivity can be increased without deteriorating the transparency, and mechanical properties such as heat resistance and impact strength can be improved all at once.

[0106] Furthermore, the molar ratio (I / T) of the first diol to the dicarboxylic acid or derivative thereof component introduced in step (a) can be 0.17 to 0.80, 0.17 to 0.65, 0.18 to 0.60, 0.18 to 0.50, 0.18 to 0.45, 0.18 to 0.42, 0.18 to 0.40, 0.19 to 0.42, 0.19 to 0.40, 0.25 to 0.40, or 0.25 to 0.40.

[0107] The molar ratio (C / T) of the second diol to the dicarboxylic acid or derivative thereof component introduced in step (a) may be 0.65-0.85, 0.65-0.82, 0.66-0.80, 0.67-0.77, 0.67-0.75, 0.72-0.77, 0.67-0.85, or 0.67-0.80.

[0108] The molar ratio (E / T) of the third diol to the dicarboxylic acid or derivative thereof component introduced in step (a) may be 0.18 to 1.50, 0.19 to 1.35, 0.20 to 1.25, 0.21 to 1.23, 0.18 to 1.10, 0.20 to 0.95, 0.20 to 0.50, 0.21 to 0.35, 0.21 to 0.33, or 0.21 to 0.32.

[0109] Since the molar ratio of the first to third diols to the dicarboxylic acid or its derivative component introduced in step (a) is adjusted within the above range, it is possible to increase the heat resistance, mechanical properties, and miscibility as well as the transparency and viscosity characteristics.

[0110] In addition, at least one additive selected from the group consisting of a colorant, a crystallization agent, an oxidation stabilizer, and a branching agent may be further added to the composition. Details regarding the additives are as described above.

[0111] The composition is then subjected to an esterification reaction (step (b)).

[0112] The esterification reaction is carried out at a pressure of 0.1 kg / cm from normal pressure. 2 ~3.0kg / cm 2 The reaction may be carried out at a pressure as high as possible and at a temperature of 245° C. to 275° C. for 2 to 12 hours.

[0113] The pressure is 0.1kg / cm above normal pressure. 2 ~3.0kg / cm 2 , 0.2kg / cm 2 ~2.5kg / cm 2 , 0.3kg / cm 2 ~2.2kg / cm 2 , 0.5kg / cm 2 ~2.0kg / cm 2 or 1.0kg / cm 2 ~2.0kg / cm 2 It may be just as expensive.

[0114] Furthermore, the esterification reaction may be carried out at a temperature of 248°C to 275°C, 250°C to 275°C, 250°C to 272°C, 255°C to 270°C, or 260°C to 268°C for 2 hours to 11 hours, 2 hours to 10 hours, 2.5 hours to 9 hours, 2.5 hours to 6 hours, or 2.5 hours to 4 hours.

[0115] More specifically, the esterification reaction is carried out by injecting nitrogen into a reactor containing the composition to maintain the pressure at 0.1 kg / cm 2 above atmospheric pressure. 2 ~3.0kg / cm 2 The method may be carried out by the steps of (b-1) setting the temperature in the reactor higher by 210° C. to 230° C. over a period of 60 to 120 minutes, (b-2) raising the temperature of the reactor from room temperature to 210° C. to 230° C. over a period of 60 to 120 minutes and then maintaining that state for 1 to 3 hours, and (b-3) raising the temperature from 245° C. to 275° C. over a period of 1 to 3 hours and then subjecting the composition to an esterification reaction.

[0116] Step (b-2) may be a step of increasing the temperature of the reactor from room temperature to 210°C to 230°C or 215°C to 225°C over a period of 70 to 110 minutes or 80 to 100 minutes, and then maintaining that state for 1 to 3 hours or 1.5 to 2.5 hours.

[0117] Upon completion of the esterification reaction, the pressure in the pressurized reactor is reduced to atmospheric pressure and the polycondensation reaction can then be carried out.

[0118] The product of the esterification reaction is then subjected to a polycondensation reaction.

[0119] The polycondensation reaction may be carried out at a pressure of 0.01 mmHg to 600 mmHg and a temperature of 260° C. to 290° C. for 1 hour to 10 hours. For example, the polycondensation reaction may be carried out at a pressure of 0.01 mmHg to 450 mmHg, 0.01 mmHg to 300 mmHg, 0.01 mmHg to 200 mmHg, 0.05 mmHg to 100 mmHg, 0.1 mmHg to 50 mmHg, 0.2 mmHg to 10 mmHg, 0.2 mmHg to 3 mmHg, 0.3 mmHg to 1.5 mmHg, or 0.5 mmHg to 1.2 mmHg and a temperature of 263°C to 290°C, 265°C to 285°C, 268°C to 285°C, 270°C to 285°C, or 275°C to 285°C for 1 hour to 8 hours or 2 hours to 6 hours.

[0120] Specifically, the polycondensation reaction can be carried out in a step (c-1) of reducing the pressure of the product of the esterification reaction from 4.0 mmHg to 6.0 mmHg over a period of 20 to 40 minutes, and a step (c-2) of increasing the temperature from 260°C to 290°C over a period of 0.5 to 2 hours, and then carrying out the polycondensation reaction while maintaining the pressure at 0.01 mmHg to 400 mmHg.

[0121] Step (c-1) may be a step of reducing the pressure of the product of the esterification reaction from 4.0 mmHg to 6.0 mmHg or from 4.5 mmHg to 5.5 mmHg over a period of 20 to 40 minutes or 25 to 35 minutes.

[0122] Further, in step (c-2), the temperature may be increased from 263° C. to 290° C., 265° C. to 285° C., 268° C. to 285° C., 270° C. to 285° C., or 275° C. to 285° C. over a period of 0.5 hours to 2 hours, or 0.7 hours to 1.2 hours.

[0123] At the beginning of the polycondensation reaction, the stirring speed can be set high. As the polycondensation reaction proceeds, if the stirring power weakens due to the increase in viscosity of the reactants or the temperature of the reactants rises above the set temperature, the stirring speed can be adjusted accordingly.

[0124] The polycondensation reaction may be carried out until the intrinsic viscosity (IV) of the polycondensation reactant is 0.65 dl / g to 0.78 dl / g, 0.64 dl / g to 0.76 dl / g, 0.64 dl / g to 0.75 dl / g, 0.68 dl / g to 0.78 dl / g, 0.70 dl / g to 0.78 dl / g, 0.70 dl / g to 0.75 dl / g, 0.72 dl / g to 0.78 dl / g, or 0.74 dl / g to 0.78 dl / g.

[0125] Additionally, catalysts and / or stabilizers may be further added in the esterification and polycondensation reactions.

[0126] For example, catalysts for the esterification reaction can be sodium and magnesium methylates, acetates, borates, fatty acid salts and carbonates of Zn, Cd, Mn, Co, Ca and Ba, metallic Mg and oxides of Pb, Zn, Sb and Ge.

[0127] Furthermore, the catalyst for the polycondensation reaction may be, for example, a titanium-based catalyst, such as tetraethyl titanate, acetyl tripropyl titanate, tetrapropyl titanate, tetrabutyl titanate, polybutyl titanate, 2-ethylhexyl titanate, octylene glycol titanate, lactate titanate, triethanolamine titanate, acetylacetonate titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, titanium dioxide / silicon dioxide copolymer, titanium dioxide / zirconium dioxide copolymer, germanium-based catalyst, such as germanium dioxide and copolymers using same, or a tin-based catalyst, such as monobutyltin oxide, dibutyltin oxide, and monobutylhydroxytin oxide.

[0128] Additionally, the stabilizer may be a phosphorus-based compound such as, but not limited to, phosphoric acid, trimethyl phosphate, and triethyl phosphate may be used.

[0129] The stabilizer may be used in an amount of 10 ppm to 500 ppm based on the total weight of the copolymerized polyester resin. For example, the stabilizer may be used in an amount of 50 ppm to 400 ppm, 70 ppm to 350 ppm, or 100 ppm to 300 ppm based on the total weight of the copolymerized polyester resin.

[0130] Furthermore, after step (b), a water washing step may be further carried out by immersing the polycondensation reaction product in water at 60°C to 80°C for 5 minutes to 7 hours. For example, after step (b), it may be carried out by immersing the polycondensation reaction product in water at 60°C to 80°C or 65°C to 75°C for 10 minutes to 7 hours, 30 minutes to 7 hours, 1 hour to 6.5 hours, 2 hours to 6 hours, 3 hours to 5.5 hours, or 4 hours to 5.5 hours. Since a water washing step is further carried out under the above conditions, the miscibility of the copolymerized polyester resin may be further increased.

[0131] The residual rate (%) of isosorbide (ISB) in the copolymer polyester resin prepared by the process for preparing a copolymer polyester resin according to one embodiment of the present invention may be 40% or more. For example, the residual rate (%) of isosorbide (ISB) in the copolymer polyester resin may be calculated by the following formula A, and may be 40% or more, 42% or more, 45% or more, 50% or more, 55% or more, or 58% or more. [Formula A] Residual rate of ISB (%)=(mol % of residues derived from ISB among all residues of 100 mol % of diol component of copolymer polyester resin / mol ratio of ISB to dicarboxylic acid or derivative component added during preparation of copolymer polyester resin)×100

[0132] The residual ratio of isosorbide represents the content of isosorbide contained in the final copolyester resin prepared by the polycondensation process relative to the content of isosorbide introduced. Since the residual ratio of isosorbide in the copolyester resin prepared by the process for preparing a copolyester resin according to one embodiment of the present invention is controlled within the above range, the heat resistance and hydrolysis resistance can be further increased without deteriorating the transparency and mechanical properties.

[0133] Aspects of the invention The present invention will now be described in more detail with reference to the following examples, which are provided to illustrate the present invention and are not intended to limit the scope of the present invention. EXAMPLES

[0134] [Example] Preparation of copolymer polyester resin Example 1 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,608.6 g (15.7 moles) of terephthalic acid (TPA), 435.9 g (3.0 moles) of isosorbide (ISB), 1,516.4 g (10.5 moles) of cyclohexanedimethanol (CHDM) and 311.7 g (5.0 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.18.

[0135] Then, 12.8 g of GeO2 as a catalyst, 5.1 g of phosphoric acid as a stabilizer, 0.020 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient), 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) and 0.4 g of trimellitic anhydride as a branching agent were added thereto, followed by stirring to prepare a composition.

[0136] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.0 kgf / cm above normal pressure. 2The temperature of the reactor was then increased by 100° C. (absolute pressure: 1,495.6 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 260° C. over 2 hours. The esterification reaction was then carried out at a temperature of 260° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0137] (c) Polycondensation reaction Thereafter, the pressure of the reactor containing the product of the esterification reaction was reduced from normal pressure to 5.0 torr (absolute pressure: 5 mmHg) over 30 minutes. At the same time, the temperature of the reactor was increased to 280°C over 1 hour, and the polycondensation reaction was carried out while maintaining the pressure of the reactor at 1.0 torr (absolute pressure: 1.0 mmHg) or less. Here, the stirring speed was set high at the beginning of the polycondensation reaction. As the polycondensation reaction proceeded, if the stirring force weakened due to an increase in the viscosity of the reactants or if the temperature of the reactants rose above the set temperature, the stirring speed was appropriately adjusted accordingly. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.75 dl / g. Then, the mixture was discharged outside the reactor to form strands. Then, they were solidified by a cooling liquid, then granulated to have an average weight of about 12 mg to 14 mg, and immersed in water at 70°C for 5 hours for water washing to prepare a copolymerized polyester resin.

[0138] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 11 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 65 mol %, and the ethylene glycol derived residues were 24 mol %.

[0139] Example 2 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,047.2 g (12.3 moles) of terephthalic acid (TPA), 450.1 g (3.1 moles) of isosorbide (ISB), 1,281.5 g (8.9 moles) of cyclohexanedimethanol (CHDM) and 174.6 g (2.8 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.20.

[0140] Then, 10.2 g of GeO2 as a catalyst and 4.1 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0141] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 0.5 kgf / cm 2 above normal pressure. 2 The temperature of the reactor was then increased by 100° C. (absolute pressure: 1,127.8 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 265° C. over 2 hours. The esterification reaction was then carried out at a temperature of 265° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0142] (c) Polycondensation reaction Thereafter, the pressure of the reactor containing the product of the esterification reaction was reduced from normal pressure to 5.0 torr (absolute pressure: 5 mmHg) over 30 minutes. At the same time, the temperature of the reactor was increased to 275°C over 1 hour, and the polycondensation reaction was carried out while maintaining the pressure of the reactor at 0.7 torr (absolute pressure: 0.7 mmHg) or less. Here, the stirring speed was set high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, if the stirring force weakened due to an increase in the viscosity of the reactants or if the temperature of the reactants rose above the set temperature, the stirring speed was appropriately adjusted accordingly. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.65 dl / g. The mixture was then discharged outside the reactor to form strands, which were solidified by a cooling liquid and then granulated to have an average weight of about 12 mg to 14 mg to prepare a copolymerized polyester resin.

[0143] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 12 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 70 mol %, and the ethylene glycol derived residues were 18 mol %.

[0144] Example 3 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,417.4 g (14.6 moles) of terephthalic acid (TPA), 382.7 g (2.6 moles) of isosorbide (ISB), 1,664.6 g (11.6 moles) of cyclohexanedimethanol (CHDM) and 294.5 g (4.8 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 1.30.

[0145] Then, 12.3 g of GeO2 as a catalyst, 4.9 g of phosphoric acid as a stabilizer, 0.019 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient) and 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) as a colorant and 3.85 g of hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0146] (b) Esterification reaction The esterification reaction was carried out in the same manner as in Example 1, step (b).

[0147] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 270° C. over 1 hour, the pressure in the reactor was maintained at 0.5 Torr (absolute pressure: 0.5 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.78 dl / g.

[0148] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 11 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 77 mol %, and the ethylene glycol derived residues were 12 mol %.

[0149] Example 4 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,400.8 g (14.5 moles) of terephthalic acid (TPA), 675.7 g (4.6 moles) of isosorbide (ISB), 1,502.9 g (10.4 moles) of cyclohexanedimethanol (CHDM) and 186.8 g (3.0 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.30.

[0150] Then, 12.3 g of GeO2 as a catalyst, 4.9 g of phosphoric acid as a stabilizer, 0.019 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient) and 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) as a colorant were added thereto, followed by stirring to prepare a composition.

[0151] (b) Esterification reaction The esterification reaction was carried out in the same manner as in Example 1, step (b).

[0152] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 270° C. over 1 hour, the pressure in the reactor was maintained at 0.2 Torr (absolute pressure: 0.2 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.70 dl / g.

[0153] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 20 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 70 mol %, and the ethylene glycol derived residues were 10 mol %.

[0154] Example 5 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,618.1 g (15.8 moles) of terephthalic acid (TPA), 967.1 g (6.6 moles) of isosorbide (ISB), 1,521.9 g (10.6 moles) of cyclohexanedimethanol (CHDM) and 303.0 g (4.9 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.40.

[0155] Then, 13.4 g of GeO2 as a catalyst, 5.4 g of phosphoric acid as a stabilizer, 0.02 g of polyethylene resin as a crystallizing agent and 6.30 g of hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0156] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.5 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 1,863.4 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 270° C. over 2 hours. The esterification reaction was then carried out at a temperature of 270° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the nitrogen in the pressurized reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0157] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 275° C. over 1 hour, the pressure in the reactor was maintained at 0.9 Torr (absolute pressure: 0.9 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.64 dl / g.

[0158] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 25 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 65 mol %, and the ethylene glycol derived residues were 10 mol %.

[0159] Example 6 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,541.1 g (15.3 moles) of terephthalic acid (TPA), 894.0 g (6.1 moles) of isosorbide (ISB), 1,636.2 g (11.4 moles) of cyclohexanedimethanol (CHDM) and 197.2 g (3.2 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.35.

[0160] Then, 13.1 g of GeO2 as a catalyst, 5.3 g of phosphoric acid as a stabilizer and 7.38 g of a hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0161] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.0 kgf / cm above normal pressure. 2 The pressure in the reactor was increased by 100% (absolute pressure: 1,495.6 mmHg). The temperature of the reactor was then increased from room temperature to 220°C over 90 minutes, maintained at 220°C for 2 hours, and then increased again to 265°C over 2 hours. The esterification reaction was then carried out at a temperature of 265°C for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0162] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 280° C. over 1 hour, the pressure in the reactor was maintained at 0.3 Torr (absolute pressure: 0.3 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.74 dl / g.

[0163] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 20 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 72 mol %, and the ethylene glycol derived residues were 8 mol %.

[0164] Example 7 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,294.8 g (11.8 moles) of dimethyl terephthalate (DMT), 1,036.2 g (7.1 moles) of isosorbide (ISB), 1,141.4 g (7.9 moles) of cyclohexane dimethanol (CHDM) and 902.0 g (14.5 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 2.50.

[0165] Then, 10.1 g of GeO2 as a catalyst and 4.0 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0166] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 0.1 kgf / cm 2 above normal pressure. 2 The pressure was increased by 100% (absolute pressure: 833.6 mmHg). The temperature of the reactor was then increased from room temperature to 220°C over 90 minutes, maintained at 220°C for 2 hours, and then increased again to 265°C over 2 hours. The esterification reaction was then carried out at a temperature of 265°C for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, the pressure in the reactor was reduced to normal pressure, and the product of the esterification reaction in the reactor was then transferred to a 7-liter reactor capable of reaction under vacuum.

[0167] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 280° C. over 1 hour, the pressure in the reactor was maintained at 0.2 Torr (absolute pressure: 0.2 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.64 dl / g.

[0168] In the copolymerized polyester resin so prepared, the dimethyl terephthalate-derived residues were 100 mol % relative to the total acid-derived residues, the isosorbide-derived residues were 25 mol % relative to the total diol-derived residues, the cyclohexanedimethanol-derived residues were 65 mol %, and the ethylene glycol-derived residues were 10 mol %.

[0169] Example 8 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 1,865.4 g (11.2 moles) of terephthalic acid (TPA), 98.2 g (0.6 moles) of isophthalic acid (IPA), 725.3 g (5.0 moles) of isosorbide (ISB), 1,141.4 g (7.9 moles) of cyclohexanedimethanol (CHDM) and 153.9 g (2.5 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.30.

[0170] Then, 10.1 g of GeO2 as a catalyst and 4.0 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0171] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.5 kgf / cm above normal pressure. 2The pressure in the reactor was increased by 100% (absolute pressure: 1,863.4 mmHg). The temperature of the reactor was then increased from room temperature to 220°C over 90 minutes, maintained at 220°C for 2 hours, and then increased again to 270°C over 2 hours. The esterification reaction was then carried out at a temperature of 270°C for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0172] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 275° C. over 1 hour, the pressure in the reactor was maintained at 0.3 Torr (absolute pressure: 0.3 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.64 dl / g.

[0173] In the copolymerized polyester resin thus prepared, the terephthalic acid-derived and isophthalic acid-derived residues were 100 mol % based on the total acid-derived residues, the isosorbide-derived residues were 25 mol % based on the total diol-derived residues, the cyclohexanedimethanol-derived residues were 65 mol %, and the ethylene glycol-derived residues were 10 mol %.

[0174] Example 9 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,182.6 g (13.1 moles) of terephthalic acid (TPA), 537.5 g (3.7 moles) of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD), 1,366.3 g (9.5 moles) of cyclohexanedimethanol (CHDM) and 243.2 g (3.9 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 1.30.

[0175] Then, 1.5 g of dibutyltin oxide as a catalyst and 4.5 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0176] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.0 kgf / cm above normal pressure. 2 The temperature of the reactor was then increased by 100° C. (absolute pressure: 1,495.6 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 268° C. over 2 hours. The esterification reaction was then carried out at a temperature of 268° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0177] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Example 2, except that the temperature of the reactor was increased to 280° C. over 1 hour, the pressure in the reactor was maintained at 0.2 Torr (absolute pressure: 0.2 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.70 dl / g.

[0178] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the 2,2,4,4-tetramethyl-1,3-cyclobutanediol derived residues were 20 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 70 mol %, and the ethylene glycol derived residues were 10 mol %.

[0179] Comparative Example 1 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,821.8 g (17.0 moles) of terephthalic acid (TPA), 397.1 g (2.7 moles) of isosorbide (ISB), 1,514.1 g (10.5 moles) of cyclohexanedimethanol (CHDM) and 496.9 g (8.0 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.25.

[0180] Then, 13.4 g of GeO2 as a catalyst, 5.4 g of phosphoric acid as a stabilizer, 0.021 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient) and 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) as a colorant were added thereto, followed by stirring to prepare a composition.

[0181] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 2.0 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 2,231.2 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 255° C. over 2 hours. The esterification reaction was then carried out at a temperature of 255° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, the pressure in the reactor was reduced to normal pressure, and the product of the esterification reaction in the reactor was then transferred to a 7-liter reactor capable of reaction under vacuum.

[0182] (c) Polycondensation reaction Thereafter, the pressure of the reactor containing the product of the esterification reaction was reduced from normal pressure to 5.0 torr (absolute pressure: 5 mmHg) over 30 minutes. At the same time, the temperature of the reactor was increased to 272°C over 1 hour, and the polycondensation reaction was carried out while maintaining the pressure of the reactor at 1.2 torr (absolute pressure: 1.2 mmHg) or less. Here, the stirring speed was set high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, if the stirring force weakened due to an increase in the viscosity of the reactants or if the temperature of the reactants rose above the set temperature, the stirring speed was appropriately adjusted accordingly. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.70 dl / g. Then, the mixture was discharged outside the reactor to form strands, which were then solidified by a cooling liquid and granulated to have an average weight of about 12 mg to 14 mg, to prepare a copolymerized polyester resin.

[0183] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 7 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 60 mol %, and the ethylene glycol derived residues were 33 mol %.

[0184] Comparative Example 2 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,511.6 g (15.1 moles) of terephthalic acid (TPA), 309.3 g (2.1 moles) of isosorbide (ISB), 1,617.2 g (11.2 moles) of cyclohexanedimethanol (CHDM) and 298.1 g (4.8 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.20.

[0185] Then, 12.5 g of GeO2 as a catalyst, 5.0 g of phosphoric acid as a stabilizer and 3.9 g of a hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0186] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 2.0 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 2,231.2 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 262° C. over 2 hours. The esterification reaction was then carried out at a temperature of 262° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0187] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 280° C. over 1 hour, the pressure in the reactor was maintained at 1.0 Torr (absolute pressure: 1.0 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.72 dl / g.

[0188] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 8 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 72 mol %, and the ethylene glycol derived residues were 20 mol %.

[0189] Comparative Example 3 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,198.6 g (13.2 moles) of terephthalic acid (TPA), 251.4 g (1.7 moles) of isosorbide (ISB), 1,631.9 g (11.3 moles) of cyclohexanedimethanol (CHDM) and 134.9 g (2.2 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.15.

[0190] Then, 11.2g of GeO2 as a catalyst, 4.5g of phosphoric acid as a stabilizer and 1.05g of trimellitic anhydride as a branching agent were added thereto, followed by stirring to prepare a composition.

[0191] (b) Esterification reaction The esterification reaction was carried out in the same manner as in Example 1, step (b).

[0192] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 282° C. over 1 hour, the pressure in the reactor was maintained at 0.5 Torr (absolute pressure: 0.5 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.65 dl / g.

[0193] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 5 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 83 mol %, and the ethylene glycol derived residues were 12 mol %.

[0194] Comparative Example 4 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,452.7 g (14.8 moles) of terephthalic acid (TPA), 690.3 g (4.7 moles) of isosorbide (ISB), 1,316.1 g (9.1 moles) of cyclohexanedimethanol (CHDM) and 331.1 g (5.3 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.30.

[0195] Then, 12.0 g of GeO2 as a catalyst, 4.8 g of phosphoric acid as a stabilizer, 0.019 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient) and 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) as a colorant and 5.63 g of hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0196] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 2.0 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 2,231.2 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 258° C. over 2 hours. The esterification reaction was then carried out at a temperature of 258° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0197] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 270° C. over 1 hour, the pressure in the reactor was maintained at 0.7 Torr (absolute pressure: 0.7 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.62 dl / g.

[0198] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 15 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 60 mol %, and the ethylene glycol derived residues were 25 mol %.

[0199] Comparative Example 5 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,222.5 g (13.4 moles) of terephthalic acid (TPA), 508.2 g (3.5 moles) of isosorbide (ISB), 1,689.4 g (11.7 moles) of cyclohexanedimethanol (CHDM) and 36.3 g (0.6 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.18.

[0200] Then, 11.7 g of GeO2 as a catalyst, 4.7 g of phosphoric acid as a stabilizer, 0.018 g of blue toner (product name: Polysynthren Blue RLS, manufacturer: Clarient) and 0.004 g of red toner (product name: Solvaperm Red BB, manufacturer: Clarient) as a colorant were added thereto, followed by stirring to prepare a composition.

[0201] (b) Esterification reaction The esterification reaction was carried out in the same manner as in Example 6, step (b).

[0202] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 285° C. over 1 hour, the pressure in the reactor was maintained at 0.4 Torr (absolute pressure: 0.4 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.61 dl / g.

[0203] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 13 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 85 mol %, and the ethylene glycol derived residues were 2 mol %.

[0204] Comparative Example 6 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,628.0 g (15.8 moles) of terephthalic acid (TPA), 1,155.7 g (7.9 moles) of isosorbide (ISB), 1,245.6 g (8.7 moles) of cyclohexanedimethanol (CHDM) and 298.0 g (4.8 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acid or derivatives thereof) was 1.35.

[0205] Then, 13.1 g of GeO2 as a catalyst, 5.3 g of phosphoric acid as a stabilizer and 7.38 g of a hindered phenolic oxidation stabilizer (product name: Irganox 1076, manufacturer: BASF) were added thereto, followed by stirring to prepare a composition.

[0206] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 2.0 kgf / cm above normal pressure. 2The temperature was then increased by 100° C. (absolute pressure: 2,231.2 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 270° C. over 2 hours. The esterification reaction was then carried out at a temperature of 270° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0207] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 278° C. over 1 hour, the pressure in the reactor was maintained at 0.2 Torr (absolute pressure: 0.2 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.64 dl / g.

[0208] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues are 100 mol % based on the total acid derived residues, the isosorbide derived residues are 28 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues are 53 mol %, and the ethylene glycol derived residues are 19 mol %.

[0209] Comparative Example 7 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,439.6 g (14.7 moles) of terephthalic acid (TPA), 1,287.4 g (8.8 moles) of isosorbide (ISB), 1,418.1 g (9.8 moles) of cyclohexanedimethanol (CHDM) and 45.5 g (0.7 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 1.32.

[0210] Then, 12.8 g of GeO2 as a catalyst, 5.1 g of phosphoric acid as a stabilizer and 0.63 g of polyethylene resin as a crystallizing agent were added thereto, followed by stirring to prepare a composition.

[0211] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.5 kgf / cm above normal pressure. 2 The pressure in the reactor was increased by 100° C. (absolute pressure: 1,863.4 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 268° C. over 2 hours. The esterification reaction was then carried out at a temperature of 263° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the nitrogen in the pressurized reactor was discharged to the outside, and the pressure in the reactor was reduced to normal pressure, and then the product of the esterification reaction in the reactor was transferred to a 7-liter reactor capable of reaction under vacuum.

[0212] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 275° C. over 1 hour, the pressure in the reactor was maintained at 0.3 Torr (absolute pressure: 0.3 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.55 dl / g.

[0213] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 32 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 65 mol %, and the ethylene glycol derived residues were 3 mol %.

[0214] Comparative Example 8 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,670.7 g (16.1 moles) of terephthalic acid (TPA), 587.2 g (4.0 moles) of isosorbide (ISB), 1,791.3 g (12.4 moles) of cyclohexanedimethanol (CHDM) and 326.4 g (5.3 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 0.68.

[0215] Then, 13.4g of GeO2 as a catalyst, 5.4g of phosphoric acid as a stabilizer and 0.63g of trimellitic anhydride as a branching agent were added thereto, followed by stirring to prepare a composition.

[0216] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.5 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 1,863.4 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 263° C. over 2 hours. The esterification reaction was then carried out at a temperature of 263° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, the pressure in the reactor was reduced to normal pressure, and the product of the esterification reaction in the reactor was then transferred to a 7-liter reactor capable of reaction under vacuum.

[0217] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 270° C. over 1 hour, the pressure in the reactor was maintained at 0.5 Torr (absolute pressure: 0.5 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.81 dl / g.

[0218] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 9 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 75 mol %, and the ethylene glycol derived residues were 16 mol %.

[0219] Comparative Example 9 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,444.6 g (13.2 moles) of terephthalic acid (TPA), 817.0 g (5.6 moles) of isosorbide (ISB), 1,268.0 g (8.8 moles) of cyclohexanedimethanol (CHDM) and 248.4 g (4.0 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 0.42.

[0220] Then, 12.2 g of GeO2 as a catalyst and 4.9 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0221] (b) Esterification reaction The esterification reaction was carried out in the same manner as in Example 6, step (b).

[0222] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 268° C. over 1 hour, the pressure in the reactor was maintained at 0.2 Torr (absolute pressure: 0.2 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.62 dl / g.

[0223] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 22 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 58 mol %, and the ethylene glycol derived residues were 20 mol %.

[0224] Comparative Example 10 (a) Preparation of the composition A 10 liter reactor equipped with a column and a condenser for cooling with water was charged with 2,253.8 g (13.6 moles) of terephthalic acid (TPA), 297.3 g (2.0 moles) of isosorbide (ISB), 1,814.0 g (12.6 moles) of cyclohexanedimethanol (CHDM) and 52.3 g (0.8 moles) of ethylene glycol (EG), where G / A (total diols / total diacids, the molar ratio of diol components to dicarboxylic acids or derivatives thereof) was 0.38.

[0225] Then, 11.8 g of GeO2 as a catalyst and 4.7 g of phosphoric acid as a stabilizer were added thereto, followed by stirring to prepare a composition.

[0226] (b) Esterification reaction Thereafter, nitrogen was injected into the reactor containing the composition to reduce the pressure in the reactor to 1.0 kgf / cm above normal pressure. 2 The temperature was then increased by 100° C. (absolute pressure: 1,495.6 mmHg). The temperature of the reactor was then increased from room temperature to 220° C. over 90 minutes, maintained at 220° C. for 2 hours, and then increased again to 270° C. over 2 hours. The esterification reaction was then carried out at a temperature of 270° C. for 3 hours while visually observing the composition in the reactor until the composition became transparent. Simultaneously with the completion of the esterification reaction, the pressurized nitrogen in the reactor was discharged to the outside, the pressure in the reactor was reduced to normal pressure, and the product of the esterification reaction in the reactor was then transferred to a 7-liter reactor capable of reaction under vacuum.

[0227] (c) Polycondensation reaction A copolymerized polyester resin was prepared in the same manner as in step (c) of Comparative Example 1, except that the temperature of the reactor was increased to 285° C. over 1 hour, the pressure in the reactor was maintained at 0.4 Torr (absolute pressure: 0.4 mmHg) or less, and the polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) reached 0.65 dl / g.

[0228] In the copolymerized polyester resin so prepared, the terephthalic acid derived residues were 100 mol % based on the total acid derived residues, the isosorbide derived residues were 8 mol % based on the total diol derived residues, the cyclohexanedimethanol derived residues were 90 mol %, and the ethylene glycol derived residues were 2 mol %.

[0229] [Test Example] Test Example 1: Composition of Copolymer Polyester Resin The copolymer polyester resins of Examples 1 to 9 and Comparative Examples 1 to 10 were each dissolved in CDCl3 solvent at a concentration of 3 mg / ml. The composition (mol%) of the copolymer polyester resin was then measured by 1H-NMR spectrum obtained using a nuclear magnetic resonance instrument (JEOL, 600 MHz FT-NMR) at 25°C.

[0230] Furthermore, the composition ratio of cyclohexanedimethanol to isosorbide (C(mol%) / I(mol%)), the composition ratio of cyclohexanedimethanol to 2,2,4,4-tetramethyl-1,3-cyclobutanediol (C(mol%) / T(mol%)), the composition ratio of cyclohexanedimethanol to ethylene glycol (C(mol%) / E(mol%)), the composition ratio of isosorbide to ethylene glycol (I(mol%) / E(mol%)), and the composition ratio of 2,2,4,4-tetramethyl-1,3-cyclobutanediol to ethylene glycol (T(mol%) / E(mol%)) were calculated from the composition (mol%) of each diol component specified above.

[0231] Test Example 2: Residual rate of ISB The residual rate (%) of ISB for each of the copolymerized polyester resins of Examples 1 to 9 and Comparative Examples 1 to 10 was calculated according to the following formula A. [Formula A] Residual rate of ISB (%)=(mol % of residues derived from ISB out of 100 mol % of all residues of diol component of copolymer polyester resin / mol ratio of ISB to dicarboxylic acid or derivative component added during preparation of copolymer polyester resin)×100

[0232] Test Example 3: Glass Transition Temperature The copolyester resins of Examples 1-9 and Comparative Examples 1-10 were each calculated for glass transition temperature (TG) using a Mettler Toledo DSC1 instrument.

[0233] Specifically, the glass transition temperature was measured as the first endothermic temperature in a second scan obtained by increasing the temperature of the copolymer polyester resin to 280° C. at 10° C. / min under nitrogen, decreasing the temperature to 30° C. at −300° C. / min, and then increasing the temperature again to 280° C. at 10° C. / min under nitrogen.

[0234] Test Example 4: Impact Strength The copolymerized polyester resins of Examples 1 to 9 and Comparative Examples 1 to 10 were each measured for impact strength (J / m) in accordance with ASTM D256.

[0235] Specifically, a sample (width: 63.3 mm, length: 12.5 mm, thickness: 3.2 mm or width: 63.3 mm, length: 12.5 mm, thickness: 6.4 mm) was prepared by injection molding the copolymer polyester resin at 250°C, and a 2.3 mm notch was formed in the center of the sample using a notch meter in accordance with ISO 2818.

[0236] Then, one end of the sample was fixed, and the other end was impacted in the cutting direction with a hammer, and the impact strength was measured using an impact strength instrument (product name: NO.258 PC-S IMPACT TESTER, manufacturer: Yasuda Seiki Seisakusho, hammer capacity: 2.75 J for a sample with a thickness of 3.2 mm or 5.5 J for a sample with a thickness of 6.4 mm). Here, it was measured 10 times, and the average value was calculated.

[0237] Test Example 5: Intrinsic Viscosity The copolymerized polyester resins of Examples 1 to 9 and Comparative Examples 1 to 10 were each dissolved in orthochlorophenol (OCP) at 100° C. at a concentration of 0.12%, and the intrinsic viscosity (IV, dl / g) was measured using an Ubbelohde viscometer in a thermostat at 35° C.

[0238] Test Example 6: Haze The copolymerized polyester resins of Examples 1 to 9 and Comparative Examples 1 to 10 were blended in a weight ratio of 1:1 as shown in the following Tables 3 to 5 to prepare samples having a thickness of 6 mm. The haze (%) of the samples was then measured using a Minolta Co., Ltd. CM-3600A instrument according to ASTM D1003-97. ◎: Haze value between 0% and less than 3.0% ○: Haze value of 3.0% to less than 5.0% ×: Haze value of more than 5.0%

[0239] [Table 1]

[0240] [Table 2]

[0241] [Table 3]

[0242] [Table 4]

[0243] [Table 5]

[0244] As shown in Tables 1 to 5 above, the copolymer polyester resins of Examples 1 to 9 were superior to the resins of Comparative Examples 1 to 10 in all of the ISB residual rate, glass transition temperature, impact strength, intrinsic viscosity, and haze properties.

[0245] Specifically, the copolymer polyester resins of Examples 1 to 9 had a high residual rate of ISB, did not deteriorate in heat resistance and transparency, and had impact strength and intrinsic viscosity controlled within specific ranges, thereby providing excellent compatibility between resins. Therefore, the copolymer polyester resins of Examples 1 to 9 can minimize waste of raw materials due to excellent compatibility between resins in the process, and when they are applied to products that require high impact strength and high heat resistance in various fields, particularly packaging materials such as food containers and automotive interior parts, they will be excellent in stability and quality.

[0246] In contrast, the resins of Comparative Examples 1 to 10 have low glass transition temperatures, resulting in low heat resistance, poor impact strength or intrinsic viscosity properties, and especially poor miscibility between resins.

[0247] Specifically, as shown in Table 3, the copolymer polyester resins of Examples 1 to 9 had very good compatibility between the resins, since the haze values ​​measured in the samples prepared by blending them with each other were all less than 5.0%.

[0248] In contrast, the resins of Comparative Examples 1 to 10 had poor compatibility, as shown in Table 4, since most of the haze values ​​measured on the samples prepared by blending with each other were above 5.0%. In some cases, when the haze value was less than 5.0%, the heat resistance or impact strength properties were not good.

[0249] Furthermore, as shown in Table 5, most of the haze values ​​measured in the samples prepared by blending with the copolymer polyester resins of Examples 1 to 9 having excellent miscibility were above 5.0%, resulting in poor miscibility. In some cases, when the haze value was less than 5.0%, the heat resistance or impact strength properties were not good.

[0250] Therefore, the resins of Comparative Examples 1 to 9 had low economic efficiency in the manufacturing process. If they are applied to products that require high impact strength and high heat resistance, such as packaging materials such as food containers and automobile interior parts, they will be inferior in stability and quality.

Claims

1. A copolymerized polyester resin comprising a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, The diol component is (1) 10 mol % to 26 mol % of a first diol comprising isosorbide (ISB) or a derivative thereof; (2) 65 mol % to 80 mol % of a second diol comprising cyclohexanedimethanol (CHDM) or a derivative thereof; (3) 8 mol % to 25 mol % of a third diol different from the first diol and the second diol; and A copolymer polyester resin, wherein a sample having a thickness of 6 mm prepared by blending two kinds of said copolymer polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% as measured according to ASTM D1003-97.

2. A copolymerized polyester resin comprising a repeating unit derived from a diol component and a repeating unit derived from a dicarboxylic acid or a derivative thereof, The diol component is (4) 15 mol % to 25 mol % of a fourth diol comprising 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD) or a derivative thereof; (5) 70 mol % to 80 mol % of a fifth diol comprising cyclohexanedimethanol (CHDM) or a derivative thereof; (6) 0 mol % to 10 mol % of a sixth diol different from the fourth diol and the fifth diol; and A copolymer polyester resin, wherein a sample having a thickness of 6 mm prepared by blending two kinds of said copolymer polyester resins having different compositions in a weight ratio of 1:1 has a haze of less than 5.0% as measured according to ASTM D1003-97.

3. The copolymer polyester resin according to claim 1 or 2, wherein the two types of the copolymer polyester resins are one type of the copolymer polyester resin according to claim 1 and one type of the copolymer polyester resin according to claim 2.

4. The copolymer polyester resin according to claim 1 or 2, having a glass transition temperature (Tg) of 98°C to 115°C.

5. A sample having a thickness of 6.4 mm prepared from the copolymer polyester resin has an impact strength of 700 J / m or more, as measured according to ASTM D256; and 3. The copolymer polyester resin according to claim 1 or 2, wherein a sample having a thickness of 3.2 mm prepared from the copolymer polyester resin has an impact strength of 800 J / m or more, as measured according to ASTM D256.

6. The copolymer polyester resin according to claim 1 or 2, having an intrinsic viscosity (IV) of 0.64 to 0.78 dl / g.

7. The third diol or the sixth diol includes at least one selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-propanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, neopentyl glycol, and derivatives thereof. The copolymerized polyester resin according to claim 1 or 2.

8. The copolymerized polyester resin according to claim 1 or 2, further comprising at least one additive selected from the group consisting of colorants, crystallization agents, oxidation stabilizers and branching agents.

9. The crystallization agent is at least one selected from the group consisting of a crystal nucleating agent, a UV absorber, a polyolefin resin, a polyamide resin, and a polyalkylene resin; and The copolymer polyester resin according to claim 8, wherein the crystallization agent is used in an amount of 0.1 ppm to 10 ppm based on the total weight of the copolymer polyester resin.

10. The oxidation stabilizer includes at least one selected from the group consisting of a hindered phenol-based oxidation stabilizer, a phosphite-based oxidation stabilizer, and a thioether-based oxidation stabilizer; and The copolymer polyester resin according to claim 8, wherein the oxidation stabilizer is used in an amount of 50 ppm to 3,000 ppm based on the total weight of the copolymer polyester resin.

11. The branching agent comprises at least one selected from the group consisting of trimellitic anhydride, trimethylolpropane, and trimellitic acid; and The copolymer polyester resin of claim 8, wherein the branching agent is used in an amount of from 100 ppm to 2,500 ppm based on the total weight of the copolymer polyester resin.

12. A process for preparing the copolymer polyester resin according to claim 1 or 2, comprising the steps of: (a) preparing a composition comprising a diol component and a dicarboxylic acid or a derivative thereof component; (b) subjecting the composition to an esterification reaction; (c) subjecting the product of the esterification reaction to a polycondensation reaction; wherein the molar ratio (G / A) of the diol component to the dicarboxylic acid or derivative thereof component introduced in step (a) is 1.10 to 3.

00.

13. The process for preparing a copolyester resin according to claim 12, wherein after step (b), a step of washing with water is further carried out by immersing the product of the polycondensation reaction in water at 60°C to 80°C for 5 minutes to 7 hours.

Citation Information

Patent Citations

  • Polyester composition containing tetramethylcyclobutanediol, cyclohexanedimethanol, and ethylene glycol, and method for producing the same.

    JP2010507716A

  • A miscible blend of terephthalate polyesters containing 1,4-cyclohexanedimethanol and 2,2,4,4-tetramethylcyclobutane-1,3-diol

    JP2012512937A

  • A ternal blend of terephthalate or isophthalate polyester containing EG, CHDM, and TMCD.

    JP2015522102A

  • Extrudable polyester copolymer

    JP2022521678A

  • Articles comprising isosorbide and processes for their manufacture

    US20150165668A1